Machinability of AISI304 stainless steel using Ethylene Glycol nano particles based coolant - Yogeswaran, Muthusamy (2015)
This thesis present the development of linear model order for predicting the milling parameter such as surface roughness, tool life and wear mechanism for end-milling operation of AISI304 stainless steel using TiN coated carbide insert with water soluble coolant and nano particle based coolant (TiO2/EG). The linear model equation of surface roughness and tool life are developed using response surface methodology (RSM). The cutting variables are cutting speed, feed rate, and axial depth. The developed linear model equations for the surface roughness tool life show that the most significant input parameter is the feed rate, followed by axial depth and cutting speed. The end-milling operation by using nano particle based coolant (TiO2/EG) obtains lower surface roughness and high tool life compared with end-milling operation by using water soluble coolant. In general, the tool failure for milling with water soluble coolant was flank wear, crater wear, crack, chipping and fracture at cutting distance of 720 mm. The milling process with nano particle based coolant (TiO2/EG) obtains a chipping and fracture and cutting distance of 1200 mm. According to ISO 8688-2-1989 (E) the wear criteria for milling with water soluble coolant reached at average of cutting distance of 800 mm but the cutting distance for milling with nano particle based coolant (TiO2/EG) reached the ISO 8688-2-1989 (E) the wear criteria at cutting distance of 1300 mm. The SEM and EDX spectrum shows there are nano layer of Ti nano particle from the nanofluid embedded and fills the holes in the insert and for a layer which act as a thermal bridge for the cutting insert. Attrition and oxidation at the cutting edge were the main tool wear mechanism present during end-milling operation nano particle based coolant (TiO2/EG). An oxide layer has been formed during the oxidation wear which shield the cutting tool from the impact during the milling process